1999
DOI: 10.1533/cras.1999.0103
|View full text |Cite
|
Sign up to set email alerts
|

Development of a side facing seat and seat belt system for the Australian Army Perentie 4×4

Abstract: The survivability of soldiers in the rear of military vehicles when involved in a crash has been identified as an area of major concern. The Australian Army via Project TRANSAFE has developed and evaluated a range of side facing Seat and Seat Belt Systems (SSBS) for the Perentie 4x4 to improve crash survivability. Options which have been evaluated include; bench seat with lap seat belt, bench seat with lap sash seat belt, individual seat with harness. wooden seat with lap sash seat belt and a plastic seat with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The data results for the collision produced with the study van type vehicle are similar to those observed by Levick et al in a collision of American ambulances 5 . The risk of chest, abdominal and head trauma were noted in both tests where the dummies were placed perpendicular to the road, a position already known to be dangerous 11 . The seatbacks should be placed parallel to the road and secured by seatbelts anchored in three points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data results for the collision produced with the study van type vehicle are similar to those observed by Levick et al in a collision of American ambulances 5 . The risk of chest, abdominal and head trauma were noted in both tests where the dummies were placed perpendicular to the road, a position already known to be dangerous 11 . The seatbacks should be placed parallel to the road and secured by seatbelts anchored in three points.…”
Section: Discussionmentioning
confidence: 99%
“…5 The risk of chest, abdominal and head trauma were noted in both tests where the dummies were placed perpendicular to the road, a position already known to be dangerous. 11 The seatbacks should be placed parallel to the road and secured by seatbelts anchored in three points.…”
Section: Discussionmentioning
confidence: 99%